2017
DOI: 10.1016/j.jip.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the adaptations of strains of Lymantria dispar multiple nucleopolyhedrovirus to hosts from spatially isolated populations

Abstract: The adaptation of pathogens to either their hosts or to environmental conditions is the focus of many current ecological studies. In this work we compared the ability of six spatially-distant Lymantria dispar (gypsy moth) multiple nucleopolyhedrovirus (LdMNPV) strains (three from eastern North America and three from central Asia) to induce acute infection in gypsy moth larvae. We also sequenced the complete genome of one Asian (LdMNPV-27/0) and one North American (LdMNPV-45/0) strain which were used for bioass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Population differences of viral entomopathogens in terms of virulence are partially determined by their genetic differences. In particular, the strains of Lymantria dispar multiple nucleopolyhedrovirus (LdMNPV, Baculoviridae) isolated in North America possess higher virulence than the Asian strain because of vef-1 gene deletion [9][10]. However, the phenotypic expression of these genetic differences does not depend on the host population [10]; conversely, it is ruled by the environmental conditions.…”
Section: Pathogen Virulence and Ecological Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Population differences of viral entomopathogens in terms of virulence are partially determined by their genetic differences. In particular, the strains of Lymantria dispar multiple nucleopolyhedrovirus (LdMNPV, Baculoviridae) isolated in North America possess higher virulence than the Asian strain because of vef-1 gene deletion [9][10]. However, the phenotypic expression of these genetic differences does not depend on the host population [10]; conversely, it is ruled by the environmental conditions.…”
Section: Pathogen Virulence and Ecological Fitnessmentioning
confidence: 99%
“…In particular, the strains of Lymantria dispar multiple nucleopolyhedrovirus (LdMNPV, Baculoviridae) isolated in North America possess higher virulence than the Asian strain because of vef-1 gene deletion [9][10]. However, the phenotypic expression of these genetic differences does not depend on the host population [10]; conversely, it is ruled by the environmental conditions. In particular, sunlight easily decreases the potency of the American strain by UV even after 15 min of exposure, while the Asian strain possesses higher UV tolerance [11].…”
Section: Pathogen Virulence and Ecological Fitnessmentioning
confidence: 99%
“…
Motivation and Aim: Nucleopolyhedroviruses (NPVs, Baculoviridae) are specific viruses of insects that are used for pest control. High variation in virus virulence depends upon genetic factors [1]. Here we compare genomes of closely related genetic variants of Lymantria dispar multiple NPV (LdMNPV) that differ in virulence.
…”
mentioning
confidence: 99%
“…Mutational analysis of ORF122, ORF7 or hr17 using SpltNPV bacmids to be constructed or via CRISPR-CAS9 mutagenesis would be required to substantiate this claim. It is interesting to note that differences in biological activity were found between spatially separated isolates of Lymantria dispar MNPV in conjunction with differences in whole genome sequence information (Harrison et al, 2016;Martemyanov et al, 2017). By applying dN/dS analysis it is possible that other virulence genes come to light, an approach that has worked well when comparing different baculovirus species (Harrison and Bonning 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, the fast acting SpltNPV isolates emerged from genogroups A and B and the genetic variability may have contributed towards fast biological activity as the small variation within genome can result in significant changes in biological activity (Cory et al, 2005). A further study demonstrated that the virulence of LdMNPV is determined only by viral genetics and not by the locality of host population (Martemyanov et al, 2017).…”
mentioning
confidence: 99%